1996
DOI: 10.1093/pasj/48.5.l41
|View full text |Cite
|
Sign up to set email alerts
|

The IRTS (Infrared Telescope in Space) Mission

Abstract: The Japanese satellite-borne infrared telescope, the Infrared Telescope in Space (IRTS), has completed a successful survey of a portion of the infrared sky. The IRTS consists of a 15 cm telescope cooled with superfluid liquid helium, and is installed on board the Space Flyer Unit (SFU) spacecraft. The SFU was launched on 1995 March 18 UT. The sky survey by the IRTS started on March 29 UT, and was completed on April 25 UT after exhausting its liquid helium. The cryogenic system operated as designed, and maintai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
25
0

Year Published

1997
1997
2013
2013

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(26 citation statements)
references
References 0 publications
1
25
0
Order By: Relevance
“…Thronson et al 1987;Claussen et al 1987;Jura & Kleinmann 1990;Noguchi et al 2004). For example, Le Bertre et al (2003) investigated the spectra of 689 AGB stars acquired in the four radial directions (l = −10 • , 50 • , 130 • , and 170 • ) with the Near-InfraRed Spectrometer (NIRS; Noda et al 1996) on-board the InfraRed Telescope in Space (IRTS; Murakami et al 1996), and found that O-rich AGB stars outnumber C-rich ones in the inner Galaxy (<8 kpc), whereas the situation is the reverse in the outer Galaxy. However, most past studies surveyed limited regions of the solar neighborhood because of their sensitivity constraints.…”
Section: Introductionmentioning
confidence: 99%
“…Thronson et al 1987;Claussen et al 1987;Jura & Kleinmann 1990;Noguchi et al 2004). For example, Le Bertre et al (2003) investigated the spectra of 689 AGB stars acquired in the four radial directions (l = −10 • , 50 • , 130 • , and 170 • ) with the Near-InfraRed Spectrometer (NIRS; Noda et al 1996) on-board the InfraRed Telescope in Space (IRTS; Murakami et al 1996), and found that O-rich AGB stars outnumber C-rich ones in the inner Galaxy (<8 kpc), whereas the situation is the reverse in the outer Galaxy. However, most past studies surveyed limited regions of the solar neighborhood because of their sensitivity constraints.…”
Section: Introductionmentioning
confidence: 99%
“…These bands, also called Aromatic Infrared Bands (AIBs), have now been observed in many places where interstellar or circumstellar matter is submitted to UV irradiation, in our Galaxy as well as in external galaxies. Many observations were performed by the recent IR space missions, in particular the Infrared Space Observatory (ISO; Kessler et al 1996) and the Infrared Telescope in Space (IRTS; Murakami et al 1996).…”
Section: Introductionmentioning
confidence: 99%
“…The IRTS has a primary mirror 15 cm in diameter, cooled with liquid helium, and succeeded in the survey observation for about one month until all the helium was consumed (Murakami et al 1996). The FarInfrared Line Mapper (FILM) is one of the focal plane instruments of the IRTS (Shibai et al 1994).…”
Section: Observations and Data Reductionmentioning
confidence: 99%